CC-002 Not just another bleeding ulcer. (23rd September 2015) - Evans, J A; Goel, R; Tibble, J
Abstract : Introduction: Isolated pancreatic tuberculosis (TB) is exceptionally rare, but increasing numbers of cases are being reported. This is attributed to the growing TB and human immunodeficiency virus (HIV) pandemic. Methods: We report a case of a 39-year-old male who presented with acute upper gastrointestinal bleeding secondary to pancreatic TB. Oesophogastroduodenoscopy (OGD) was undertaken showing a duodenal ulcer with duodenitis. He was discharged on regular proton pump inhibitor for 6 weeks. 3 months later he was referred by his GP for further investigation of recurrent abdominal pain and deranged liver function tests. Ultrasound and CT showed a pancreatic mass and a diagnostic laparoscopy with omental biopsy for suspected pancreatic carcinoma was performed. Results: Omental biopsies revealed widespread granulomatous inflammation and staining for acid fast bacilli was positive. There was no pulmonary involvement and HIV testing was negative. CT scan and follow-up OGD after 12 months of anti-tuberculous treatment showed complete resolution. The range of differential diagnoses, histopathological findings, investigative difficulties and treatment options are discussed. Conclusion: Pancreatic TB is difficult to diagnose due to the way it mimics a range of other conditions. Pancreatic TB should be considered as a differential diagnoses for a pancreatic mass especially in patients who have travelled to or from areas where the disease is endemic. With appropriate treatment pancreatic TB shows excellent response rates and can obviate unnecessary surgery.